The dynamics of place branding in Johannesburg: 1994 - 2019 - Mbinza, Zenzile (University of the Witwatersrand, Johannesburg, 2023)
This PhD thesis lays the ground for understanding place branding processes from cities of the Global South. It critically explores place branding as an emerging mechanism for urban governance in Johannesburg. It is critical because place branding and its related processes have increasingly gained momentum in countries, regions and cities jostling for niche status in global economics. This thesis explores the different place brands that Johannesburg coined over time, focussing on the period between 1994 and 2019. It explored the city’s place brands under the five mayors that presided over Johannesburg, beginning with Dan Pretorius (1994 – 1995), Isaac Mogase (1995 – 1999), Amos Masondo (2000 – 2011), Parks Tau (2011 – 2016) and Herman Mashaba (2016 – 2019). The thesis employed a qualitative research methodology and case study design. Primary data Archival research and interviews were the primary data collection strategies. The ensuing discussion of place brands in Johannesburg reveals the dynamics and push factors that have contributed to the development of place brands under the time in question. Politics, economics, and activities related to globalisation emerged as leading drivers for the city of Johannesburg to develop its various place brands. The thesis found that Johannesburg followed a template similar to the cities of the Global North in its application of place branding. However, the thesis also found gaps in the city’s place branding processes. For example, there was limited engagement with the city residents when developing Johannesburg’s place brands. It pointed to a unilateral, top-down application of place branding in the city, which precluded it from using these processes as democracy-building tools. It necessitates the exploration of place branding from the perspective of city governments to begin encompassing issues of inclusivity and public participation. In this light, the thesis calls for a more strategic application of place branding in the Johannesburg.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Urban and Regional Planning, to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Place branding; Johannesburg; Democracy; World-class-African city aspirational; Identity; UCTD; SDG-11: Sustainable cities and communities; SDG-9: Industry, innovation and infrastructure